Socialization of The Use of Used Plastic Bottles as a Model of The Human Respiratory System for Elementary School Children - Setiani, Nurul; Wakinah, Wakinah; Nurazizah, Suci; Siti Sumirah; Qadrsih, Nabilah Rahma; Zakiyah, Zakiyah; Uswah, Uswah; Dirgantara, Marvinda Rizki (UrbanGreen Central Media, 2025)
This community development aims to invite elementary school children from grades 3 to 6 in the Griya Yasa housing complex, to be able to utilize plastic bottle waste as a demonstration tool for the human respiratory system. Where in the Griya Yasa housing complex, plastic bottle waste in each house is collected. The use of plastic bottle waste as a demonstration tool for the human respiratory system aims to train the creativity of elementary school children and be able to apply science lessons on the human respiratory system. Where the production of plastic waste in Indonesia continues to rise annually in line with population growth. Plastic waste is one of the main environmental issues in this decade. The result of this community service for elementary school children is the importance of being able to utilize used goods to make demonstration tools. The children were very enthusiastic in making it.